1997
DOI: 10.2466/pms.1997.85.3.803
|View full text |Cite
|
Sign up to set email alerts
|

The Multidimensional Dream Inventory: Preliminary Evidence for Validity and Reliability

Abstract: The present study focused on the development of the Multidimensional Dream Inventory, an individual difference measure of dimensions of dreams. Items were administered to 151 college students. Consistent with expectations, results of an exploratory factor analysis of intercorrelations among items indicated a four-factor solution was appropriate. As a result, four dream-relevant scales were constructed, viz, Dream Importance, Dream Vividness, Dream Usefulness, and Dream Recall. In addition, these scales showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Groth-Marnat, 1990). Interestingly, although several studies assessing the reliability of questionnaires have been reported in the field of dream research (e.g., Soper et al, 1990;Kallmeyer & Chang, 1997; Kroth, Yonida, & Hammond, 1998;Agargün et al, 1999;Bruni et al, 1999), reliability issues within the methodology of dream content analysis are rarely investigated.Schredl (1998) determined the internal consistency of selected dream characteristics (e.g., bizarreness, positive and negative emotions, and number of dream persons) 1 To whom correspondence and reprint requests should be addressed. …”
mentioning
confidence: 99%
“…Groth-Marnat, 1990). Interestingly, although several studies assessing the reliability of questionnaires have been reported in the field of dream research (e.g., Soper et al, 1990;Kallmeyer & Chang, 1997; Kroth, Yonida, & Hammond, 1998;Agargün et al, 1999;Bruni et al, 1999), reliability issues within the methodology of dream content analysis are rarely investigated.Schredl (1998) determined the internal consistency of selected dream characteristics (e.g., bizarreness, positive and negative emotions, and number of dream persons) 1 To whom correspondence and reprint requests should be addressed. …”
mentioning
confidence: 99%
“…And if it happens in the future, as if our feelings off without limits while sleeping at the time and place without knowing...!!! [1][2][3][4][5][6] Perhaps this happen also in the feeling of waking, some people sees such events that occur in real life, does this mean that they live in after the fourth for a moment of time. And not the fourth dimension of time end targets dimensional.…”
Section: Why and How Are We Dreaming?mentioning
confidence: 99%
“…In this case, only we can share with the past, present, and future. To illustrate, we are going to sleep, our minds and our feelings in dimensions other than that we know are awake, and it is the people who think in his sleep events that may occur after h and days or months [1][2][3][4][5][6][7].…”
Section: Why and How Are We Dreaming?mentioning
confidence: 99%
See 2 more Smart Citations